Source apportionment of PM2.5 bound Polycyclic Aromatic Hydrocarbons from a Tricity in the foothills of Himalayas in Northern India - Sandeep Garg; Anita rajor; Amit Dhir (International Journal of Science and Engineering, 2019)
This study highlights variability in mass levels and source identification of PM2.5 bound polycyclic aromatic hydrocarbons (PAHs) in the tricity of Chandigarh, Mohali and Panchkula in India. The samples of PM2.5 werecollected from industrial and residential and sensitive receptor sites during summer (April-May 2015) and winter (December 2015-January 2016) season. Sampling was done using medium volume sampler and chemical analysis was done using gas-chromatography technique. The average mass levels of PM2.5 varied from 31 to 91 µg m-3 exceeding to NAAQ standard of 60µg m-3 and total PAHs varied from 5.76 to 75.62 ngm-3 with a seasonal variability as higher in winter than in summer season. The positive correlation between PM2.5 & TPAHs suggested similarity in source and origin. Diagnostic ratio and principal components analysis suggested vehicular emissions, coal combustion, wood and biomass burning as the main source of PAHs in the study area for potential health hazards.